Sweep-Soil Interaction: a Mathematical Model. Issue 1 (April 2021) - Zaripova, N A; Soyunov, A S; Algazin, D N; Kulaeva, A G; Kuzmin, D E
Abstract: Cutting-edge tillage machinery design involves the evolving theory of implement-soil interaction. This paper proposes a mathematical model that represents the performance indicators of a sweep (soil deformation, draught, contact pressure) as a function of design and operating factors (note: this paper covers low-crown sweeps). Analysis of these equations and the results of field experiments show that increasing the nose angle will reduce the drag and require less force to cut the stubbles. As the cutting angle increases, more force is required to cut through; the penetration ability is directly proportional to cos α .